WAYS OF PHILOSOPHY DEVELOPMENT: A SIGHT FROM THE SILVER AGE - Суходуб, Т. Д. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
The article reveals the conceptual approaches of the philosophers of the «Russian Silver Age» to understanding the tasks of philosophy and ways of its development. The theme of the «strength» and «weakness» of philosophy is actualized in the aspect of its ability to respond to the spiritual and cultural and historical «challenges» of the modern age. Scientific interests constitute the teachings of I.I. Lapshin, N.O. Lossky, G.G. Shpet et al. Draws attention that in the «new» understanding of philosophy a special role belongs to «ontological turn». It is concluded that the basis of historical development of philosophy is the same problem namely definition of the meanings of theoretical and practical philosophy, their delimitation and connection. Beyond this issue the solution of the problems of human existence is difficult.